BRAND STRENGTH FOR MICRO, SMALL,AND MEDIUM ENTERPRISES - I Nyoman Tri Sutaguna; Hardi Fardiansyah; Eka Hendrayani; Muhammad Yusuf (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This research is to find out about brand strength for Micro, Small and Medium Enterprises in West Java in the form of Brand Image and Identity and Brand Identity on Brand Love. This study used the AMOS SEM analysis method with a total of 147 respondents from Alunicorn consumers throughout Indonesia. The result of his research is that the influence of Brand Image and Identity is in the same direction as Brand Love.